﻿Validated ion exchange HPLC method for the quantification of levothyroxine - a narrow therapeutic index drug - used for the treatment of hypothyroidism - Marwa Al Jamal; Malak Al Bathish; Azza Gazy (Pensoft Publishers, 2023)
Drugs with narrow therapeutic index (NTI-drugs) have been defined by the FDA as drugs with small differences between therapeutic and toxic doses that might lead to serious therapeutic failures or life-threatening adverse drug reactions. Levothyroxine sodium pentahydrate (LT4), a synthetic T4 hormone used for the treatment of hypothyroidism (a condition where there is a hormonal imbalance in the thyroid gland that is responsible for the regulation of several physiological, metabolic, cardiovascular, and neurological processes). LT4 is designated by the FDA as a narrow therapeutic index drug and is available in the market in the form of very low dose pharmaceutical formulations ranging from 25 mcg to 150 mcg. This requires that the pharmaceutical dosage form should contain the exact labeled amount of the active ingredient, LT4, such that safety and efficacy are maintained. Therefore, it is necessary to develop an a precise, accurate and sensitive analytical method for LT4 quantification considering the treatment doses being in micrograms. In the present work, an ion exchange HPLC method has been developed and validated for the determination of LT4 as per ICH guidelines. The developed method was found to be simple, sepcific, precise and accurate. The low LOD and LOQ values allowed the quantitfication of the active ingredient in different pharmaceutical products qualifying the method to be applied in quality control assays.